2019
DOI: 10.1108/ijlss-10-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and implementation potential of the lean concept in the petroleum industry: state-of-the-art

Abstract: Purpose A systematic literature review is performed to reveal the state-of-the-art in the implementation of lean principles in the petroleum industry. This paper aims to generate a conceptual framework and reveal research gaps with respect to lean concept application in the petroleum industry. Design/methodology/approach After formulating research questions, the search strategy is generated, followed by data extraction, literature review and synthesis of the results. The search covers any studies in peer-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 101 publications
(196 reference statements)
0
10
0
1
Order By: Relevance
“…While it is well established that EPC performance can be improved by applying the lean construction model since it reveals the interdependencies of the Engineering, Procurement, and Construction phases (Ballard 1993), the application of lean concepts and tools in the specialized EPC Oil and Gas industry is still immature and lacks thoroughness. For instance, a systematic literature review by Rachman et al (2018) on the state-of-the-art implementation of lean principles in the petroleum industry revealed that lean tools and techniques improved operational and technical aspects, contractor/supplier relationships, team organization and project management practice, and that the primary benefits included substantial cycle time reduction and cost savings. However, the authors found the subject to be still immature and lacking thoroughness in research methodologies as well as showing deficiency in the descriptions of the lean tools and techniques used.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is well established that EPC performance can be improved by applying the lean construction model since it reveals the interdependencies of the Engineering, Procurement, and Construction phases (Ballard 1993), the application of lean concepts and tools in the specialized EPC Oil and Gas industry is still immature and lacks thoroughness. For instance, a systematic literature review by Rachman et al (2018) on the state-of-the-art implementation of lean principles in the petroleum industry revealed that lean tools and techniques improved operational and technical aspects, contractor/supplier relationships, team organization and project management practice, and that the primary benefits included substantial cycle time reduction and cost savings. However, the authors found the subject to be still immature and lacking thoroughness in research methodologies as well as showing deficiency in the descriptions of the lean tools and techniques used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EPC projects in the Oil and Gas industry are characterized by their large sizes, uniqueness, intricate complexities, severe risks, and involvement of numerous stakeholders i.e., clients, contractors, suppliers, etc. (Rachman et al, 2018). The Oil and Gas industry currently faces daunting challenges as schedules and budgets are becoming tighter due to oil price high volatility and market instability.…”
Section: Introductionmentioning
confidence: 99%
“…A metodologia Lean visa otimizar processos utilizando a menor quantidade de recursos possĂ­vel (tempo, equipamento, força de trabalho e espaço), sempre mantendo a qualidade e melhoria da cadeia de produção, juntamente com suas questĂ”es tĂ©cnicas e operacionais, organização dos trabalhadores e gerenciamento de processos (Rachman et al, 2018).…”
Section: Introductionunclassified
“…Belhadi et al (2018) determined trends in the research regarding Lean in SMEs, identified the gaps in the literature, and suggested future research areas for Lean in SMEs, based on studies published between 1986 and 2018. Rachman and Ratnayake (2019) formulated a conceptual framework and revealed research gaps with respect to Lean application in the petroleum industry, based on studies published between 1990 and 2017. Staedele et al (2019) built knowledge about performance evaluation in LP and made suggestions for future scientific research, based on studies published from 2000 to 2018.…”
Section: Introductionmentioning
confidence: 99%